2013
DOI: 10.7314/apjcp.2013.14.2.909
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carbohydrate Antigen 19-9 as an Indicator of Liver Metastasis in Colorectal Carcinoma Cases

Abstract: Purpose: The liver is the organ to which colorectal carcinomas (CRCs) most commonly metastasize, and surgical resection has been established as the most effective and potentially curative treatment for CRC with liver metastasis (LM). Therefore, surveillance of LM is vital for improvement of prognosis of CRC patients. In this study, we aimed to explore the potential value of carbohydrate antigen 19-9 (CA 19-9), carcinoembryonic antigen (CEA), and marker enzymes in indicating LM with CRC. Methods: Three groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
(24 reference statements)
3
15
0
Order By: Relevance
“…35% to 58% following the resection of colorectal liver metastases, with a median survival ranging from 33 to 46 months (Castaing et al, 2009;Hsu et al, 2011;Dong et al, 2013). Disease-free survival was 17.9% at 5 years, consistent with the 5-year disease-free survival rates of 15% to 25% reported in the literature (Castaing et al, 2009;Hsu et al, 2011).…”
Section: Figure 3 Overall Survival Curve For 22 Patients Who Underwesupporting
confidence: 81%
See 2 more Smart Citations
“…35% to 58% following the resection of colorectal liver metastases, with a median survival ranging from 33 to 46 months (Castaing et al, 2009;Hsu et al, 2011;Dong et al, 2013). Disease-free survival was 17.9% at 5 years, consistent with the 5-year disease-free survival rates of 15% to 25% reported in the literature (Castaing et al, 2009;Hsu et al, 2011).…”
Section: Figure 3 Overall Survival Curve For 22 Patients Who Underwesupporting
confidence: 81%
“…The liver is the most frequent (approximately 33%) metastatic site (Van Cutsem et al, 2006;Cui et al, 2013). Colorectal liver metastases (CLM) are present in 15% to 25% of cases at the time of diagnosis of the primary tumor (synchronous metastases), and approximately half of the patients undergoing radical resection of CRC will develop metastatic disease (metachronous metastasis) (Van Cutsem et al, 2006;Dong et al, 2013). Nearly 50%-60% of patients with colorectal cancer will eventually develop metastatic disease during the course of their disease (Van Cutsem et al, 2006;Hsu et al, 2011;Dong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that the survival decreased among patients with high pre-operative CEA levels and that the pre-operative CEA was correlated with tumor, tumor invasion depth, lymph node condition, stage, and post-operative recurrence (Wang et al, 2007). Many studies reported that when evaluated together, CEA and CA 19-9 levels increase sensitivity and specificity and that high levels indicate poor prognosis, where PFS and OS decreased significantly (Dixon et al, 2003;Wang et al, 2007;Sun et al, 2009;Dong et al, 2013;Sisik et al, 2013). Some studies conducted on CA 19-9 reported that it was of greater sensitivity than CEA in case of advanced stage diseases (Wang et al, 2002;Mourtzikou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, they did not find a correlation between increased CEA value and advanced TNM stage, however, there was a statistically significant correlation between increased CA 19-9 value and advanced stage. In another study Hang Dong et al (2013) suggested that the CA 19-9 might be a potential valuable indicator for liver metastasis of colorectal carcinom in the clinic.This shows the correlation between advaned stage colorectal cancer and high values of CA 19-9. Harada et al (1994) studied tumor markers in 52 gastric cancer patients and found the following positivity rates: 9.6% for CEA, 2.3% for AFP, 25% for CA 19-9, and 8.1% for CA 125.…”
Section: Discussionmentioning
confidence: 99%